THE EFFECT OF HUMAN RESOURCE MANAGEMENT STRATEGIES ON THE ORGANIZATIONAL CREATIVITY OF MEDICAL AND NURSING STAFF-AN APPLIED STUDY AT KING KHALED HOSPITAL IN SAUDI ARABIA- - Ahmed Yahya Mohsen Alrashah; Hamad. Mohammed Alhendi; Saleh Mahdi Alsulimaan; Rizq Mohammed Rizq Al Ishaq; Abdulmohsen Yahya Mohsen Al Rashah; Yassin Ghaleb Hassan Alnbzah; Mohmmed Mohsen R Alrashah; Shaker Mohsen Rizq (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
The study aimed to identify the effect of human resources management strategies in its dimensions (recruitment, training, motivation, performance appraisal strategy) on the organizational creativity of the medical and nursing staff. The study adopted the descriptive approach through a questionnaire that was applied to (250) individuals working in three hospitals at King Khaled Hospital. The study results showed that there is a high degree of appreciation for human resources management strategies at King Khaled Hospital, where this is due to the efficiency of its dimensions. The study showed that the performance appraisal strategy was in the first rank, while in the second rank came after the training strategy, and in the third rank was after the recruitment strategy, where those dimensions were at a high level of appreciation. In the fourth and final rank came after the motivation strategy at moderate level of appreciation. The study also found a statistically significant effect of the human resources management strategies (recruitment, training, motivation, performance appraisal strategy) on the organizational creativity of the medical and nursing staff at King Khaled Hospital .In light of the results, the study recommended to strengthen the strategy of human resources management in King Khaled Hospital.